Jordan : First Review Under the Extended Fund Facility Arrangement and Request for a Waiver of Nonobservance and Modifications of Performance Criteria, and Rephasing of Access-Press Release; Staff Report; and Statement by the Executive Director for Jordan. (IMF Staff Country Reports; Country Report ;, 2021)
Timely containment, a large monetary stimulus, and targeted fiscal measures helped save lives and livelihoods during the first COVID-19 wave, but a significant second wave is still unfolding. The economic and human impact has been sizeable: real GDP is expected to decline by 3 percent in 2020; unemployment has surged to record levels; tourism and remittances have declined; and revenues of the central government and of other public sector entities have dropped, raising public debt to 90 percent of GDP. A new government and parliament have been ushered in, with welcome continuity in reform commitment.